2009
DOI: 10.1103/physrevlett.102.014503
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer by Inertial Waves during the Buildup of Turbulence in a Rotating System

Abstract: We study the transition from fluid at rest to turbulence in a rotating tank. The energy is transported by inertial wave packets through the fluid volume. These high amplitude waves propagate at velocities consistent with those calculated from linearized theory [H. P. Greenspan, (Cambridge University Press, Cambridge, England, 1968)]. A "front" in the temporal evolution of the energy power spectrum indicates a time scale for energy transport at the linear wave speed. Nonlinear energy transfer between modes is g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 14 publications
(17 reference statements)
2
34
1
Order By: Relevance
“…Since the rotation of the reference frame occurs along a single direction, the symmetry between the stabilisation characteristics of eddies with cyclonic and anti-cyclonic vorticity starts to break apart [9,19], resulting in the cyclonic dominance mentioned earlier. Mathematically, this condition of small Ro and high Re, permits the reduction of (1) to a wave-like equation where the Coriolis term gives rise to inertial waves -the linear propagation of which is crucial 30 in explaining the formation of columnar structures [3,2,10]. This theory is supported by findings in physical [17, for example] and numerical [16, among others] experiments.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Since the rotation of the reference frame occurs along a single direction, the symmetry between the stabilisation characteristics of eddies with cyclonic and anti-cyclonic vorticity starts to break apart [9,19], resulting in the cyclonic dominance mentioned earlier. Mathematically, this condition of small Ro and high Re, permits the reduction of (1) to a wave-like equation where the Coriolis term gives rise to inertial waves -the linear propagation of which is crucial 30 in explaining the formation of columnar structures [3,2,10]. This theory is supported by findings in physical [17, for example] and numerical [16, among others] experiments.…”
Section: Introductionmentioning
confidence: 70%
“…Detailed analysis of the experimental observations showed that, among the columnar eddies, the cyclonic ones, which spin in the same direction as the bulk rotation, dominate the oppositely spinning anti-cyclones [7]. The presence of these columnar eddies were also found to reduce the turbulence 10 dissipation rate compared to an equivalent non-rotating case. However, very few studies, if any, address the case where the rotation is not of a solid-body type.…”
Section: Introductionmentioning
confidence: 94%
“…[41] and [42] for more recent realizations, using fractal grids). Other forcings have been used with similar results, like arrays of tubes acting as sinks and sources [43][44][45] and electromagnetic forcing (see Fig. 3(d)) [37,46,47].…”
mentioning
confidence: 96%
“…[4] and [33]). In recent years, a series of rotating platforms of smaller diameters have been set up in different laboratories, with comparable values of Re/Ro, in Austin (Texas) [38], Orsay (France) [31,50], Cambridge (United Kingdom) [34], Turin (Italy) [51], Eindhoven (Netherlands) [37], Zurich (Switzerland) [41], Tel Aviv (Israel) [44], etc. (see Table 1).…”
mentioning
confidence: 99%
“…Cambon, Mansour &Godeferd 1997 andSmith &Waleffe 1999) and the possible role of linear wave propagation (e.g. Staplehurst, Davidson &Dalziel 2008 andKolvin et al 2009), yet their results will feed into the discussion.…”
Section: Overviewmentioning
confidence: 99%